Innovative Rice Seed Coating (Oryza Sativa) with Polymer Nanofibres and Microparticles Using the Electrospinning Method - Castañeda, Letícia M.F.; Genro, Cayane; Roggia, Isabel; Bender, Stefan S.; Bender, Renar J.; Pereira, Cláudio N. (Journal of Research Updates in Polymer Science, 2014)
Seed treatments are chemical or biological substances that are applied to seeds to control infection by disease-causing organisms, insects, or other pests. Seed treatment reduces production costs of seedlings, reduces the consumption of seeds, facilitates mechanization of sowing and improves the seedling establishment. The generation of nanofibres and microcapsules by the electrospinning technique is a novel approach for active ingredient controlled release. The study evaluates an innovative rice seed coating (Oryza sativa) with polymer nanofibres and microparticles using this method. Materials and Methods: Polymer nanofibres and microcapsules were applied by the electrospinning technique to irrigated rice seeds. The treatments consisted of: 1) Control, 2) Negative control - Polymer based microcapsule without fungicide. 3) Polymer based microcapsule with fungicide. Microbiological assays and germination tests were performed following the guidelines of the Seed Analysis Rules of the Ministry of Agriculture. Results: The applied polymer as a coating did not affect the physiological quality of the seeds, as attested by the result of the germination tests, and they proved to be effective in the control of fungi disease in crop seeds. Conclusion: The germination and phytosanitary characteristics were improved in the analyzed study.